Influence of Post Covid Change In Consumer Behaviour of Millennials On Advertising Techniques and Practices - Rashi, Prakriti; Ankur Singh Bist; Ari Asmawati; Mukti Budiarto; Yustika Prihastiwi, Wahyu (Pandawan, 2021)
The pandemic caused by Covid 19 has kicked off survival strategies from vulnerable groups of people to small businesses, which has challenged the core operating practices and modified consumption patterns. Thus, effective marketing strategies are imperative in these times, that not only convey values of the brand but also resonate with people. Market disruptions are most likely to impact millennials and Gen Z and given the exploration and spending propensity, millennials are most likely to drive demand during the pandemic as well as in the post pandemic world. This research proposal aims to explore how consumer habits have changed during pandemic, how likely these habits will stick in the post pandemic world and how advertising needs to be transformed which relates best with millennials. The methodology involves a detailed analysis of literature and gathering insights from social media sites through big data. This research investigates the impact of avoiding deterministic automatisms purchasing processes, implying the need to understand, from an academic and conceptual standpoint, the utility of the set of business strategies to truly influence consumer purchasing behaviour of Millennials.